ANALYSIS OF THE FLYPAPER EFFECT AND ITS INFLUENCE ON DISTRICT/CITY REGIONAL EXPENDITURES IN ACEH PROVINCE 2016-2021 - Rahmatillah; Marzuki; Ghazali Syamni; Nurlela (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This study aims to analyze the Flypaper Effect and its Effect on District/City Regional Expenditures in Aceh Province in 2016-2021. The data used in this study is panel data. The data analysis method used is panel data regression analysis with model selection techniques using the Chow test and the Hausmant test. The results of the research on General Allocation Funds and local revenue have a positive and significant effect on district/municipality regional expenditures in Aceh Province, special allocation funds and revenue-sharing funds have no effect on district/city regional expenditures in Aceh Province. Based on the results of the study, it shows that there is a flypaper effect on district/municipal expenditures in Aceh Province.